2019
DOI: 10.1021/acs.jpcc.9b01784
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanocages for Selective Carbon Dioxide Conversion under Visible Light

Abstract: Artificial photosynthesis for CO2 conversion to fuels and value-added chemicals is a tactic to close the anthropogenic carbon cycle. To this end, developing efficient catalysts composed of earth-abundant, economic, and eco-friendly elements is desirable but challenging. By comprehensive ab initio calculations, we show for the first time that caged silicon clusters doped by vanadium atom (VSi n , n = 12–15) can catalyze CO2 hydrogenation to various C1 products (i.e., carbon monoxide, formic acid, formaldehyde, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Generally speaking, our proposed strategy for activating the inert BN cages by encapsulating a small number of transition metal atoms is universal for BN nanomaterials in which the B atoms with both occupied and unoccupied p statessimilar to the d states of transition metalsare able to accept and donate electrons during a catalytic reaction. These results complement our previous findings that the p-state electrons of nonmetal elements can be effectively activated by strategies such as doping, creating defects, nanostructuring, encapsulation with metal atoms or clusters, and hybridizing with metals or metal compounds. , Our systematic works show that nonmetal nanomaterials composed of earth abundant and nontoxic p-block elements hold great promise for various catalytic processes, and their activity can be tailored at the atomic precision.…”
Section: Resultssupporting
confidence: 88%
“…Generally speaking, our proposed strategy for activating the inert BN cages by encapsulating a small number of transition metal atoms is universal for BN nanomaterials in which the B atoms with both occupied and unoccupied p statessimilar to the d states of transition metalsare able to accept and donate electrons during a catalytic reaction. These results complement our previous findings that the p-state electrons of nonmetal elements can be effectively activated by strategies such as doping, creating defects, nanostructuring, encapsulation with metal atoms or clusters, and hybridizing with metals or metal compounds. , Our systematic works show that nonmetal nanomaterials composed of earth abundant and nontoxic p-block elements hold great promise for various catalytic processes, and their activity can be tailored at the atomic precision.…”
Section: Resultssupporting
confidence: 88%
“…In surface chemistry and catalysis, the d-band center model has been successfully used to describe interactions between transition-metal and small molecules. , Most recently, similar to the d-band center, the p band center has been applied to interpret the interaction between nonmetal atoms and gaseous adsorbates. For comparison, we constructed the Si-doped nanosheets with the SiN 3 , SiB 3 , or SiC 3 impurity center, respectively, based on the h-BN and graphene sheets. Here, the center of the p band may account for the adsorption behavior of CO 2 on these Si-doped nanosheets.…”
Section: Methodsmentioning
confidence: 99%
“…For example, hydroxyapatite in bones plays a key role in biomineralization, biocompatibility and osteoconductivity. 59,60 For instance, it has been recently shown that magnetic nanoparticles conjugated with nerve growth factor significantly promote neurite outgrowth increasing the complexity of neuronal branching trees. 61 Another reported advantage of magnetic scaffolds is that subjecting them to timevarying magnetic fields generate stresses at the microscopic level to the tissue forming cells, which is of special interest for the growth of mechano-responsive tissues.…”
Section: Scaffoldsmentioning
confidence: 99%